'Can't be what you can't see' : the transition of Aboriginal and Torres Strait Islander students into higher education : final report 2013. - Kinnane, Stephen; Wilks, Judith; Wilson, Katie; Hughes, Terri; Thomas, Sue (Australia. Office for Learning and Teaching, 2014)
This report presents the findings of an investigation into the processes, the data, the key issues, the pathways, the enablers, the constraints and the opportunities regarding the transition of Aboriginal and Torres Strait Islander students into higher education. Through an examination of qualitative and quantitative evidence, the report explores the nuances, dimensions and different perspectives of what constitutes successful transition to higher education from a range of Indigenous community contexts and diverse university settings. Four specific groups of Aboriginal and Torres Strait Islander population were also identified as being under-represented in relation to higher education: women as primary carers, young men, people in the prison system, and people with disabilities. Issues affecting these specific groups and specific efforts to enhance their transition to higher education are also discussed where appropriate. [Executive summary, ed]